Benzimidazole functionalization enables efficient multi-resonance TADF with accelerated spin-flipping and balanced charge transport - Ji-Hua Tan; Si-Wei Chen; Xin-Lu Li; Han-Nan Shi; Xiao-Long Liu; Yao-Zu Su; Xiaofeng Wang; Jun-Hua Zhuang; Chengxiang Shi; Jia-Ming Jin; Shaoyun Yin; Jia-Xiong Chen; et al. (Chemical Engineering Journal, 2026)

Short-range and long-range charge transfer based narrowband deep blue organic fluorescence emitters with EQE > 20% and CIEy ≈ 0.04 - Wenyan Zhao; Zijian Chen; Jihua Tan; Zhenyue Duan; Danhong Zhou; Yanping Huo; Jiuyan Li; Ruifang Wang; Pengzhong Chen; Xiaojun Peng (Chemical Engineering Journal, 2026)

Direct screening of multifunctional Bacillus amyloliquefaciens for fiber degradation, antifungal activity, and its role in promoting wheat straw decomposition and peanut seedling growth - Yifei Guan; Miao Zhang; Guofang Wu; Yaoke Duan; Xuan Luo; Emmanuel Afirifa Tenakwa; Naana Mintaah Akufo; Yanping Wang; Lei Wang; Zhongfang Tan (Systems Microbiology and Biomanufacturing, 2026)

Aliovalent Mg2+ doping in CdIn2S4 activates sulfur vacancies and promotes p-p orbital hybridization to enhance photocatalytic CO2 reduction - Yi Liu; Raotong Wen; Zuofang Yao; Bing Leng; Zebin Yu; Hongxiang Zhu; Yikai Wang; Xinqiu Tan; Yanping Hou; Shuangfei Wang (Journal of Environmental Chemical Engineering, 2026)

Non-invasive Computational Techniques for Diagnosing Myocardial Ischemia: Challenges and Future of FFRCT/iFRCT - Bao Li; Jincheng Liu; Yang Yang; Hao Sun; Chi Zhu; Leo Hwa Liang; Zijie Wang; Luyao Fan; Suqin Huang; Xueke Li; Guangfei Li; Liyuan Zhang; et al. (Annals of Biomedical Engineering, 2026)

Selenium-Enriched Lactiplantibacillus plantarum ZZU 8–12 Regulates Intestinal Microbiota and Inhibits Acute Liver Injury - Yanping Wang; Hengyu Ma; Haolong Li; Yuhang Huang; Yupeng Tang; Xiaoxue Tang; Pintian Sun; Zhongfang Tan; Huili Pang; Fengyuan Yang (Probiotics and Antimicrobial Proteins, 2025)

Efficient activating peracetic acid by copper-aluminum composites to degrade sulfathiazole: The critical role of Cu(III) species - Yuxiao Mu; Yanping Ding; Linli Tan; Qiulin Shi; Lei Chen; Jiaqi Ding; Jingwen Wang; Yong Liu; Pengchao Xie (Journal of Environmental Chemical Engineering, 2025)

Cobalt doping modulation of Cs4MnBi2Cl12 double perovskite induces spin polarization for boosting photocatalytic reduction of CO2 - Yan Huang; Yujia Liu; Yi Liu; Xinqiu Tan; Yikai Wang; Qian Xiao; Xiaoyu Tong; Jinghui Pan; Zebin Yu; Zuofang Yao; Yanping Hou (Chemical Engineering Journal, 2025)

Polyphenylene molecular engineering enables highly efficient multi-resonance thermally activated delayed fluorescence emitters with quenching resistance - Longjiang Xing; Xiaofeng Wang; Xiaolong Liu; Wen-Cheng Chen; Shihao Liu; Siwei Chen; Mengke Li; Ji-Hua Tan; Jia-Ming Jin; Ruicheng Wang; Shangru Li; Shaomin Ji; et al. (Chemical Engineering Journal, 2025)

Treatment of kiwifruit with Lactiplantibacillus pentosus CW5 cell-free supernatant maintains postharvest quality and alters the surface microbiome - Yuxuan Hao; Huili Pang; Haoxin Lv; Guofang Wu; Jianbo Zhang; Xuan Luo; Miao Zhang; Yaoke Duan; Yuting Hou; Yanping Wang; Lei Wang; Yimin Cai; et al. (Postharvest Biology and Technology, 2025)

Critical review on food packaging strategy against spoilage - Lei Liu; Youwei Jiang; Kun Wan; Yanping Wei; Du Tuo; Chuanqin Zhou; Quanguo He; Yimin Tan (Food and Humanity, 2025)

Postharvest fragrance dynamics of different scented cut lilies: Insights from HS–SPME–GC–MS and electronic nose - Yiwei Zhou; Yiwei Chen; Jinfeng Dong; Qin Wang; Fulong Yan; Jianjun Tan; Yechun Xu; Genfa Zhu; Yanping Fan; Yuanjun Ye (Postharvest Biology and Technology, 2025)

Integrating network pharmacology and experimental verification to explore the pharmacological mechanisms of phlorizin against osteoarthritis - Yi Yao; Qiuling Zhong; Yanping Zhong; Zixin Gao; Bo Zhou; Chun Lu; Li Zheng; Feiying Yin; Manli Tan (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

DGA ameliorates severe acute pancreatitis through modulating macrophage pyroptosis - Xiyue Yue; Lunmeng Lai; Ruina Wang; Lulu Tan; Yanping Wang; Qing Xie; Yunsen Li (Inflammation Research, 2024)

A Novel N Self-Doped Porous Biochar Synthesized by KHCO3-Activated Chicken Feather for the Remediation of Tetracycline-Contaminated Water and Soil - Yu Deng; Jingfan Chen; Zhidan Xiao; Jiaying Liu; Jie Zhang; Bingqi Zhu; Xiaotong You; Fuquan Ni; Tianqi Ao; Yanping Tan (Water, Air, & Soil Pollution, 2024)

Impact of cobalt recycling on China's electrification process: Assessing the potential reduction in cobalt demand from battery recycling - Lilong Chen; Xin Li; Yanping Luo; Wenli Tan; Qiaoying Ma; Minxi Wang; Jianbo Yang (Journal of Cleaner Production, 2024)

Understanding quality differences between kiwifruit varieties during softening - Fan Yang; Renkai Zhao; Jiangtao Suo; Yuduan Ding; Jiawei Tan; Qinggang Zhu; Yanping Ma (Food Chemistry, 2024)

A multifunctional emitter with synergistical adjustment of rigidity and flexibility for high-performance data-recording and organic light-emitting devices with “hot exciton” channel - Guowei Chen; Wen-Cheng Chen; Yaozu Su; Ruicheng Wang; Jia-Ming Jin; Hui Liang; Bingxue Tan; Dehua Hu; Shaomin Ji; Hao-Li Zhang; Yanping Huo; Yuguang Ma (Chemical Engineering Journal, 2024)

Occurrence of microplastic pollution in rivers globally: Driving factors of distribution and ecological risk assessment - Yanping Tan; Jiangyu Dai; Shuwen Xiao; Zhiqiang Tang; Jianmin Zhang; Shiqiang Wu; Xiufeng Wu; Yu Deng (Science of The Total Environment, 2023)

Nitrogen addition regulates the growth of Pinus tabuliformis by changing distribution patterns of endogenous hormones in different organs - Yuhang Peng; Keli Chen; Guoliang Wang; Jiawei Tan; Furong Wei; Yanping Ma (New Forests, 2023)

Release of metal elements from clays during elution with EDTA: Insights into the side effects of washing contaminated sites - Xueji You; Chaomeng Dai; Shuguang Liu; Yanping Duan; Bo Tan; Yalei Zhang (Applied Clay Science, 2023)

An overview of the direct and indirect effects of acid rain on plants: Relationships among acid rain, soil, microorganisms, and plants - Yan Zhang; Jiahong Li; Junyan Tan; Wenbin Li; Bhupinder Pal Singh; Xunan Yang; Nanthi Bolan; Xin Chen; Song Xu; Yanping Bao; Daofei Lv; Anan Peng; et al. (Science of The Total Environment, 2023)

A magnetic adsorbent with metal-organic framework based on ammonium phosphomolybdenum heteropoly tungstate (AWP): Selective adsorption of Rb+ and Cs+ from aqueous resources and stripping with ammonium salts - Yanping Wang; Kexin Li; Liang Ma; Dezhen Fang; Miao Lu; Xiushen Ye; Haining Liu; Huifang Zhang; Xiaoli Tan; Zhijian Wu (Hydrometallurgy, 2023)

Clean technology investment considering synergistic effects: a case from the steel sintering process - Jianxin Guo; Xianchun Tan; Xiaoyan Meng; Yanping Li (Environment, Development and Sustainability, 2022)

Host adaptation of codon usage in SARS-CoV-2 from mammals indicates potential natural selection and viral fitness - Yanan Fu; Yanping Huang; Jingjing Rao; Feng Zeng; Ruiping Yang; Huabing Tan; Zhixin Liu; Weixing Du; Long Liu (Archives of Virology, 2022)

Microplastic Contamination on the Beaches of South China - Bingwen Chai; Yanping Li; Li Wang; Xiao-Tan Zhang; Yi-Ping Wan; Fengyuan Chen; Jie Ma; Wenlu Lan; Ke Pan (Frontiers in Marine Science, 2022)
Microplastics (MPs) have emerged as a pollutant of significant global concern. The sandy beach is a fragile environment that deserves our special attention with regard to MP contamination, as this area is a hotspot that accumulates large quantities of plastic waste. Notably, our current understanding of the MP distribution on beaches and the scale of contamination is far from sufficient. Hence, this study investigated the occurrence and characteristics of MPs on 14 beaches along the coast of South China. The MPs were ubiquitously distributed in the sand, most were small, less than 1 mm. A total of 18 types of polymers were identified in the sand, suggesting that diverse types of MPs are present on the beaches. Polyethylene, polypropylene, and polystyrene were the dominant types of MPs in most of our sampling sites. The MP abundance was higher in the upper layers (0–20 cm) of the beach than in the deeper layers (20–40 cm) of the sampling site when characterized by depth (Yangjiang beach). Our study demonstrates the extent and severity of MP pollution on the beaches of South China and provides implications for future remediation measures. More effort is needed to clarify the vertical distribution of MPs on beaches, especially for those MPs less than 1 μm.

Probiotic Potential and Wide-spectrum Antimicrobial Activity of Lactic Acid Bacteria Isolated from Infant Feces - Xing Wang; Weidong Wang; Haoxin Lv; Hua Zhang; Yuan Liu; Miao Zhang; Yanping Wang; Zhongfang Tan (Probiotics and Antimicrobial Proteins, 2021)

Three-dimensional reconstruction of Picea wilsonii Mast. pollen grains using automated electron microscopy - Weiwei Shen; Lingyu Ma; Xi Zhang; Xixia Li; Yuanyuan Zhao; Yanping Jing; Yun Feng; Xueke Tan; Fei Sun; Jinxing Lin (Science China Life Sciences, 2020)

Genetic diversity and pathogenicity dynamics of Magnaporthe oryzae in the Wuling Mountain area of China - Xin Xu; Wu Yang; Ke Tian; Jie Zheng; Xinqiong Liu; Kai Li; Wei Lu; Yanping Tan; Yonghua Qin; Chuntai Wang (European Journal of Plant Pathology, 2019)

Root order-dependent seasonal dynamics in the carbon and nitrogen chemistry of poplar fine roots - Hongying Chen; Yufeng Dong; Tan Xu; Yanping Wang; Huatian Wang; Baoli Duan (New Forests, 2017)

Growth and yield of oleic sunflower (Helianthus annuus L.) under drip irrigation in very strongly saline soils - Shuqin Wan; Yanping Jiao; Yaohu Kang; Shufang Jiang; Junli Tan; Wei Liu; Jing Meng (Irrigation Science, 2013)

Genetical and molecular analysis reveals a cooperating relationship between cytoplasmic male sterility- and fertility restoration-related genes in Oryza species - YanPing Tan; ShaoQing Li; HongWei Xie; ShiHua Duan; Ting Wang; YingGuo Zhu (Theoretical and Applied Genetics, 2011)

Brief report: a new profile of terminal N-acetyllactosamines glycans on pig red blood cells and different expression of α-galactose on Sika deer red blood cells and nucleated cells - Yingxia Tan; Feng Gong; Subo Li; Shouping Ji; Yanping Lu; Hongwei Gao; Hua Xu; Yangpei Zhang (Glycoconjugate Journal, 2010)

Gametophytically alloplasmic CMS line of rice (Oryza sativa L.) with variant orfH79 haplotype corresponds to specific fertility restorer - Shaoqing Li; Yanping Tan; Kun Wang; Cuixiang Wan; Yingguo Zhu (Theoretical and Applied Genetics, 2008)

Overexpression of SBPase enhances photosynthesis against high temperature stress in transgenic rice plants - Lingling Feng; Kun Wang; Yang Li; Yanping Tan; Jin Kong; Hui Li; Yangsheng Li; Yingguo Zhu (Plant Cell Reports, 2007)